Peran Pendidikan Kewarganegaraan di Era Revolusi Industri 4.0 - Siti Zahra Al Munawaroh; Dinie Anggraeni Dewi (Journal on Education, 2021)
This research is intended to determine the role of Citizenship Education in the Industrial Revolution Era 4.0. The research method uses a qualitative approach with literature study methods from reliable sources. The era of the Industrial Revolution 4.0 was indeed very influential in every aspect of life. Everything becomes easier and instant. However, the impact of the 4.0 industrial revolution was not always good. There are many negative sides to the advancement of the internet. What is the role of Citizenship Education in the era of the industrial revolution 4.0? Is Citizenship Education still relevant to be implemented at this time? Citizenship education must remain present as a breath of fresh air from the deterioration of the nation's morals due to technological advances. The Indonesian nation must maintain its national identity in the life of the nation and state.